Influences of ALDH2 on Cardiomyocyte Apoptosis in Heart Failure Rats Through Regulating PINK1-Parkin Signaling Pathway-Mediated Mitophagy: Influences of ALDH2 on Cardiomyocyte Apoptosis - Abudureyimu, Miyesaier; Zhao, Lifang; Luo, Xuanming; Wang, Xiang; Liu, Haibo (Cellular and Molecular Biology, 2022)
The study aimed to investigate the influences of aldehyde dehydrogenase 2 (ALDH2) on cardiomyocyte apoptosis in heart failure (HF) rats through regulating the PTEN induced putative kinase 1 (PINK1)-Parkin signaling pathway-mediated mitophagy. The rat model of HF was established, and the rats were randomly divided into model group (HF model, n=20) and ALDH2 group (intervention with ALDH2, n=20), with a normal group (n=20) set. After successful modeling, MRI and ECG were applied to detect the cardiac function indexes of the rats. The myocardial function index creatine kinase (CK) was measured, the status of myocardial tissue injury was determined using hematoxylin and eosin staining, and the apoptosis was observed via terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) staining. The activity of ALDH2 was detected, and the expression levels of genes and proteins were measured through quantitative polymerase chain reaction (qPCR) and Western blotting assay. The model group had notably decreased fractional shortening (FS) and ejection fraction (EF) and remarkably increased left ventricular end-diastolic diameter (LVEDD) and left ventricular end-systolic diameter (LVESD) compared with the normal group (p<0.05). The activity of ALDH2 declined obviously in the model group. The myocardial tissue injury was severer in the model group, and the number of apoptotic cells in myocardial tissues was greater in the model group than that in other groups (p<0.05). The model group manifested higher expression levels of Caspase-3 and light chain 3 (LC3) than the ALDH2 group (p<0.05) but significantly lower expression levels of PINK1, Parkin and B-cell lymphoma-2 (Bcl-2) (p<0.05). In comparison with those in the model group, the protein expression levels of PINK1, Parkin and Bcl-2 in myocardial tissues were prominently higher in the ALDH2 group (p<0.05). ALDH2 can inhibit cardiomyocyte apoptosis in HF rats by activating the PINK1-Parkin signaling pathway-mediated mitophagy, which is conducive to the recovery of HF.